2023
DOI: 10.3389/fmicb.2023.1164511
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a highly virulent Metarhizium strain targeting the tea pest, Ectropis obliqua

Abstract: IntroductionTea is one of the most widely consumed beverages around the world. Larvae of the moth, Ectropis obliqua Prout (Geometridae, Lepidoptera), are one of the most destructive insect pests of tea in China. E. obliqua is a polyphagus insect that is of increasing concern due to the development of populations resistant to certain chemical insecticides. Microbial biological control agents offer an environmentally friendly and effective means for insect control that can be compatible with “green” and organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…In this study, M. phasmatodeae , first reported in Korea and previously documented in Thailand and China, has demonstrated pathogenicity for stick insects as hosts ( Thanakitpipattana et al, 2020 ; Zhao et al, 2023 ), suggesting its potential as a promising biocontrol agent. Our observation revealed that all insects inoculated with M. phasmatodeae succumbed within 5 days.…”
Section: Discussionsupporting
confidence: 50%
“…In this study, M. phasmatodeae , first reported in Korea and previously documented in Thailand and China, has demonstrated pathogenicity for stick insects as hosts ( Thanakitpipattana et al, 2020 ; Zhao et al, 2023 ), suggesting its potential as a promising biocontrol agent. Our observation revealed that all insects inoculated with M. phasmatodeae succumbed within 5 days.…”
Section: Discussionsupporting
confidence: 50%
“…Specifically, for the soil-mixing method, the LC 50 values for the late instar larvae were 1.83 × 10 7 and 3.76 × 10 2 conidia/ml at 7 and 11 DPI, respectively. In earlier studies involving M. pingshaense, the LC 50 values were 9.6 × 10 4 and 9.1 × 10 5 conidia/ml for the larvae of the moth species Ectropis obliqua and C. punctiferalis, respectively (Zhao et al 2023). However, comparing the results of different studies is complicated by the diversity in the fungal isolates, insect pests, inoculation methods, and incubation temperatures.…”
Section: Discussionmentioning
confidence: 86%
“…Ectropis obliqua (Geometridae, Lepidoptera) is a severe leaf-feeding and polyphagous pest that feeds on a wide range of host plants, such as tea, soybean, sesame, and flowers . It is a lepidopteran moth species and is considered one of the most destructive insect pests of tea in China, , causing losses of more than 60% in tea yield and quality . As a result, E.…”
Section: Introductionmentioning
confidence: 99%